Methodology of computed tomography of maxillofacial and craniocerebral regions by means of vertical fixation of the examined objects - Anatolii Oshurko; Ihor Oliinyk; Oleksandr Tsyhykalo (The Moldovan Medical Journal, 2017)
Background: The research aims at identifying new methodological approaches to the study of morphological patterns of prenatal development of the human upper jaw. Material and methods: A working model has been developed and a device has been proposed, reasonable to be used for fixation of the examined object in a vertical position during computed tomography of maxillofacial and craniocerebral regions. For proper operation of the device there was introduced a method of vertical fixation of the examined objects during computed tomography of maxillofacial and craniocerebral regions. Results: In the basis of the useful model lies the task to develop a method of vertical fixation of objects under study during the computed tomography of maxillofacial and craniocerebral regions by holding the examined object of up to 540 mm in size; the object is fixed to the planetable using the right and left retainers that are fixed in vertical openings; the height is regulated with the help of the rack, connecting the planetable with the tripod; swivel mounting is led to the facial part of the examined object and the chin is fixed on the table; then the vertical and horizontal position of the chin is regulated by means of sliding vertical and horizontal mounting; the fixed examined object is then moved to the CT scanner with the help of mobile tripod supports. Conclusions: The proposed method is effective for vertical fixation of examined objects during the computed tomography of maxillofacial and craniocerebral regions in the desired position, that contributes to getting qualitative indicators of the examination and can be used during the spot-film radiography in direct and lateral projections in stable and desired position of the head and at the correct distance without imposing additional densities (shades) to provide accurate diagnostic results.